(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Inclusive education requires effective strategies to ensure the active participation of learners with special needs. This study explores the role of low-energy games as a pedagogical tool for increasing engagement among special needs learners in inclusive classroom settings. Using a mixed-methods approach, the research was conducted in inclusive primary classrooms, involving both qualitative observations and quantitative measures of student participation and attention.